Interspecific Competition and Complementation is a Function of N Management in Maize‐Pea Intercropping Systems. Issue 6 (6th October 2016) - Zhao, Cai; Chai, Qiang; Zhao, Yanhua; Mu, Yanping; Zhang, Yan; Yu, Aizhong; Feng, Fuxue; Liu, Chang; Yin, Wen; Hu, Falong
Abstract : Intercropping as an effective system for increasing crop yield. However, little is known about how the two intercrops compete for resources under resource‐limiting environments. Here, we quantified the competitiveness of the intercrops in response to soil available N during their co‐growth period, and determined the complementary effect of one intercrop to the other. A long‐season maize was alternated in field strips with a short‐season pea under four (N0, N1, N2, and N3) N management systems in northwestern China in 2012 and 2013. The maize‐pea intercropping, coupled with N application, can enhance crop yield. Compared with N0 treatment, N application increased the competitiveness of intercropped maize to pea by 18 to 33% during the co‐growth period. After pea harvest, the intercropped maize obtained a complementary effect, where it was grown under N0, N1, N2, and N3 managements increased the growth rate by 20, 21, 11, and 17%, respectively, compared with monoculture maize. The yield of intercropping system is a quadratic relationship with the interspecies competitiveness, with the competitiveness value of –0.059 to –0.076 being most conducive to improve the grain yield. We conclude that the treatment on 20% of the total amount of N top‐dressed at maize jointing, 50% at pretasseling, and the remaining N topdressed 10 d postflowering provided the greatest benefits for minimizing intercrop competitiveness while enhancing the complementary effect among the four N managements investigated.